NEED FOR COGNITION DAN IKLAN : TINJAUAN SIKAP KONSUMEN TERHADAP PRODUK - Madyawati, Lilis Madyawati (Jurnal Analisis Bisnis Ekonomi, 2004)
Consumer attitude represent the individual evaluation supporting, do not support or neutral to an object. Consumer atitude to product lapped over by for 3 component, that is cognate component, afeksi component, and conative component. This article explain 1) How far consumer attitude to product which one the market and how big belief of subjek or consumer to product excellence which on the market 2) Contain the evaluation subjek to product which one on the market 3) Existence of positive attitude of subjek to product which one on the market. Atitude o produc own characeristic as result learn the something that degraded. Consumer attitude to hand in glove product of its bearing with the consumer attitude to advertisement. Advertisement represent on of effort form the product bargain, where about consumer have to prosess this information accurately and circumstantial. Individual need of a kind of yhis named by Need for Cognition. By NFC, consumer attention of at higher advertisement.